Differences in Students' Computational Thinking Mathematical Ability Using Augmented Reality Based on Gender - Angraini, Lilis Marina; Sthephani, Aulia (International Journal of Contemporary Studies in Education, 2024)
This study aims explicitly to look at differences in computational thinking and mathematical ability of students who received learning with augmented reality media based on gender. Background Problems: This research is motivated by students’ low mathematical Computational Thinking (CT) ability and the rapid development of information technology in the digital era. Augmented Reality is a technology that combines three-dimensional virtual objects into a natural environment and then projects these virtual objects in real-time. The research subjects were 30 class VII students of SMPN 34 Pekanbaru in the 2022/2023 school year, randomly selected. This research was conducted on flat geometric materials, especially triangles and quadrilaterals. The data collection methods used a test of mathematical computational thinking ability. Parametric statistical tests processed test results data. The results showed differences in computational thinking and mathematical ability of students who received learning using augmented reality media based on gender. Male students’ computational thinking and mathematical ability are better than female students.